Chronic Allergen Challenge Induces Corticosteroid Insensitivity With Persistent Airway Remodeling and Type 2 Inflammation - Lewis, Brandon W.; Ford, Maria L.; Khan, Aiman Q.; Walum, Joshua; Britt, Rodney D. (Frontiers in Pharmacology, 2022)
Type 2-high severe asthma is described as a distinct endotype with Th2 inflammation, high eosinophil lung infiltration, impaired lung function, and reduced corticosteroid sensitivity. While the inflammatory milieu is similar to mild asthma, patients with type 2-high severe asthma likely have underlying mechanisms that sustain asthma pathophysiology despite corticosteroid treatments. Acute and chronic allergen models induce robust type 2 inflammatory responses, however differences in corticosteroid sensitivity remains poorly understood. In the present study, we sensitized and challenged mice with ovalbumin (OVA; acute model) or mixed allergens (MA; chronic model). Corticosteroid sensitivity was assessed by administering vehicle, 1, or 3 mg/kg fluticasone propionate (FP) and examining key asthmatic features such as airway inflammation, remodeling, hyperresponsiveness, and antioxidant capacity. Both acute and chronic allergen exposure exhibited enhanced AHR, immune cell infiltration, airway inflammation, and remodeling, but corticosteroids were unable to fully alleviate inflammation, AHR, and airway smooth muscle mass in MA-challenged mice. While there were no differences in antioxidant capacity, persistent IL-4+ Th2 cell population suggests the MA model induces type 2 inflammation that is insensitive to corticosteroids. Our data indicate that chronic allergen exposure is associated with more persistent type 2 immune responses and corticosteroid insensitivity. Understanding differences between acute and chronic allergen models could unlock underlying mechanisms related to type 2-high severe asthma.